ANALISIS MINAT SISWA TERHADAP LAGU DAERAH PADA KELAS V A SDN GAYAMSARI 02 SEMARANG - Maftuhah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the analysis of students' interest in folk songs in class V A students at SDN Gayamsari 02 Semarang. The research was conducted at SDN Gayamsari 02 Semarang with a total of 24 students in class V A for the 2022/2023 academic year. The method used is descriptive and qualitative. The questionnaire contains 20 statement items. The purpose of giving a questionnaire is to find out how students' interest in regional songs is. The result of this study is that students still lack interest in folk songs. This is reflected in the overall average of 40.10% in the less category. The results of the questionnaire were also corroborated by interviews conducted by the researcher with the class V A teacher.